High global food prices-- The challenges and opportunities: IFPRI 2007-2008 Annual Report Essay - Sheeran, Josette (International Food Policy Research Institute, 2008)
High food prices are not only causing a humanitarian crisis, but also putting at risk the development potential of millions of people. Global agriculture markets are undergoing structural changes, and the next three to four years will pose great challenges for achieving an affordable and accessible food supply for the world's most vulnerable. Soaring food and fuel prices are creating a "perfect storm" for the world's most vulnerable. The consequence is that the bottom billion could become the bottom 2 billion overnight, as those living on US$1 a day see their purchasing power cut in half.